Interactions between the Aggregatibacter actinomycetemcomitans secretin HofQ and host cytokines indicate a link between natural competence and interleukin-8 uptake - Ahlstrand T; Torittu A; Elovaara H; Välimaa H; Pöllänen MT; Kasvandik S; Högbom M; Ihalin R (Taylor & Francis, 2022)
Naturally competent bacteria acquire DNA from their surroundings to survive in nutrient-poor environments and incorporate DNA into their genomes as new genes for improved survival. The secretin HofQ from the oral pathogen Aggregatibacter actinomycetemcomitans has been associated with DNA uptake. Cytokine sequestering is a potential virulence mechanism in various bacteria and may modulate both host defense and bacterial physiology. The objective of this study was to elucidate a possible connection between natural competence and cytokine uptake in A. actinomycetemcomitans. The extramembranous domain of HofQ (emHofQ) was shown to interact with various cytokines, of which IL-8 exhibited the strongest interaction. The dissociation constant between emHofQ and IL-8 was 43 nM in static settings and 2.4 μM in dynamic settings. The moderate binding affinity is consistent with the hypothesis that emHofQ recognizes cytokines before transporting them into the cells. The interaction site was identified via crosslinking and mutational analysis. By structural comparison, relateda type I KH domain with a similar interaction site was detected in the Neisseria meningitidis secretin PilQ, which has been shown to participate in IL-8 uptake. Deletion of hofQ from the A. actinomycetemcomitans genome decreased the overall biofilm formation of this organism, abolished the response to cytokines, i.e., decreased eDNA levels in the presence of cytokines, and increased the susceptibility of the biofilm to tested β-lactams. Moreover, we showed that recombinant IL-8 interacted with DNA. These results can be used in further studies on the specific role of cytokine uptake in bacterial virulence without interfering with natural-competence-related DNA uptake.